1993
DOI: 10.1177/000331979304400706
|View full text |Cite
|
Sign up to set email alerts
|

Budd-Chiari Syndrome: Analysis of 30 Cases

Abstract: The authors report their experience with 30 adult patients with Budd-Chiari syndrome (BCS), which is a rare and serious disorder, characterized by hepatic outflow obstruction caused by many different conditions. The diagnosis was based on the clinical data, ultrasonography (US), vena cavography and hepatic venography, computed tomography (CT), and liver biopsy. Behçet's disease (BD) was found in 10 patients with BCS as an underlying disease. Two patients used oral contraceptive drugs, 2 had liver tumor hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In fact, BD is the most common cause of Budd-Chiari syndrome in Turkey [62]. There is a male predominance and the patients are younger than those with Budd-Chiari due to myeloproliferative disorders [63].…”
Section: Gastrointestinal (Gi) Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, BD is the most common cause of Budd-Chiari syndrome in Turkey [62]. There is a male predominance and the patients are younger than those with Budd-Chiari due to myeloproliferative disorders [63].…”
Section: Gastrointestinal (Gi) Diseasementioning
confidence: 99%
“…There is a male predominance and the patients are younger than those with Budd-Chiari due to myeloproliferative disorders [63]. It may present with hepatomegaly, ascites, and involvement of other great vessels, mostly venous [62]. Obstruction of the IVC is found in most patients with Budd-Chiari; the latter is due to extension of the thrombus to the ostium of the hepatic veins [63].…”
Section: Gastrointestinal (Gi) Diseasementioning
confidence: 99%
“…The incidence of Behçet’s disease as a cause of Budd–Chiari syndrome is reported to be between 2% and 5.8%. A study by Sahin et al reported Behçet’s disease as the third most common cause of the Budd–Chiari syndrome 8,9…”
Section: Discussionmentioning
confidence: 99%
“…Budd-Chiari syndrome can produce a mass lesion in the acute stage due to hemorrhagic necrosis [13,14], and Bayraktar et al [15] reported the disappearance of these lesions on follow-up. In case 2, an irregular cystic lesion with a thick wall was found in the right lobe of the liver, consistent with an area of necrosis.…”
Section: Discussionmentioning
confidence: 99%